Steady Wind Load on External Surface and Its Effect on Wind-Induced Response for a 200 m High Natural-Draught Cooling Tower - Yunfeng Zou; Fanrong Xue; Xuhui He; Chenzhi Cai; Shouke Li (Shock and Vibration)
Wind tunnel tests were carried out to measure the wind pressure of a 200 m high natural-draught cooling tower. An analysis of the distribution characteristics of external pressure was then conducted to determine the pressure coefficients Cp(θ, z) in a given wind profile. Finally, the effect on the response of the shell and the buckling safety of the shell, applying the simplified height-constant pressure coefficient Cp(θ) and the realistic pressure Cp(θ, z), was determined. Taking the wind load specified in the code as an example, the influence of the distribution of external pressure on the wind-induced response was further analyzed. The results indicate that the pressure distribution varies with not only the height z but also the circumferential angle θ, and the wind load of both ends of the tower is significantly greater than that of its middle. Moreover, the wind-induced static responses of the tower under the action of the realistic pressure distribution Cp(θ, z) and the simplified approach Cp(θ) are basically consistent, because the wind load distribution is more important than its magnitude for the wind-induced response of cooling tower, and the wind-induced response of the cooling tower is dominated by the local shell deformation.